ANALYSIS OF THE USE OF TEACHING MODULES TO INCREASING READING LITERACY IN PENDAS UPBJJ UT PADANG STUDENTS - Harnon Harnon; Muhammadi Muhammadi; Yusrafiddin Yusrafiddin (Sensei International Journal of Education and Linguistic, 2023)
True education is something that has a role as a foundation in human life. Therefore, the implementation of both formal and non-formal education must be carried out as well as possible and oriented towards the future of students. Education has the main goal of becoming a medium for developing potential and educating students, in this case students, so that they are ready to face life in the future. The era of globalization which is full of challenges, especially the world of education, requires students to be able to master literacy. It is known that literacy is an ability possessed by a person, both the ability to read, write, listen and speak. And what becomes one of the most important literacy in students is reading. Where reading is one of the language skills that must be possessed by students. Through the use of the teaching modules used, it is hoped that reading literacy will increase. This study aims to find out how the use of teaching modules increases reading literacy in PENDAS UPBJJ UT Padang students. Researchers used a qualitative descriptive approach. Data collection techniques are by interview, observation, and documentation. The module is one of the teaching aids used by students in the lecture process. The existence of teaching modules can present new learning variants and make learning more understandable and reading activities can develop.